2001
DOI: 10.1002/1096-911x(20010101)36:1<67::aid-mpo1017>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of neuroblastoma with partial deletion in the short arm of chromosome 1

Abstract: Thus, we propose three loci, 1p36.1-2, 1p32-34, and 1p36.3, as the candidate loci of neuroblastoma suppressor genes on chromosome 1p responsible for groups I, LT, and ST, respectively. Among them, the 1p32-34 locus may be associated with aggressiveness of tumor progression, possibly due to MYCN amplification and/or telomerase reactivation, while the remaining two loci may not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In human neuroblastomas, a high percentage (Ϸ28-47%) contain deletions of chromosome 1p (28)(29)(30)(31). Analyses of such chromosome deletions suggest that there may be tumor-suppressor gene(s) in the region 1p36.1-1p36.3, which contains both DFF40͞CAD and DFF45͞ICAD (29,(31)(32)(33)(34). In agreement with this finding is a report showing the homozygous deletion of DFF45 in neuroblastoma cell lines (7).…”
Section: Discussionmentioning
confidence: 99%
“…In human neuroblastomas, a high percentage (Ϸ28-47%) contain deletions of chromosome 1p (28)(29)(30)(31). Analyses of such chromosome deletions suggest that there may be tumor-suppressor gene(s) in the region 1p36.1-1p36.3, which contains both DFF40͞CAD and DFF45͞ICAD (29,(31)(32)(33)(34). In agreement with this finding is a report showing the homozygous deletion of DFF45 in neuroblastoma cell lines (7).…”
Section: Discussionmentioning
confidence: 99%
“…The CDKN2C (INK4C/p18) gene is located at 1p32, which is outside the smallest region of overlap (SRO) for 1p deletions in this study. Still this region is frequently deleted in neuroblastoma, and the 1p32 region has been suggested to play a role in neuroblastoma development (Hiyama et al, 2001). In our cohort of neuroblastoma, loss of 1p32 correlated with decreased CDKN2C expression (P ¼ 0.03, t-test), suggesting that copy number defects add to the decreased expression of CDKN2C.…”
Section: Cell Cycle Genes In Neuroblastomamentioning
confidence: 99%
“…Upon studying neuroblastoma patient samples, Hiyama et al proposed the presence of a neuroblastoma tumour suppressor gene on Chromosome 1 loci, deletion of which links to aggressiveness of the tumour (Hiyama et al, ). Fong et al also observed that loss of heterozygosity in the Chromosome 1 short arm leads to aggressive neuroblastomas (Fong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During this process, one of the transfections resulted in development of a line that showed full trisomy of Chromosome 1 and a deletion of small fragment q23 to qter of Chromosome 11. As the sample was collected after full term delivery of the baby, the abnormality is expected to have originated either during (Hiyama et al, 2001). Fong et al also observed that loss of heterozygosity in the Chromosome 1 short arm leads to aggressive neuroblastomas (Fong et al, 1989).…”
Section: Discussionmentioning
confidence: 99%